Chile's Integration Strategy: Achievements and Challenges Over 50 Years of Economic Opening (1973-2023) - Schwerter Pinto, Karin; Solar Fuentes, Diego; Sossdorf, Fernando (Latin American Journal of Trade Policy, 2024)
Chile's trade policy has been a cornerstone of its economic development model, enabling the country to overcome the limitations of its domestic market through international integration. This article examines Chile's trade integration strategy over the period 1973-2023, identifying the key milestones and transformations in its trade policy. Through a historical and methodological approach, the analysis covers the evolution from the neoliberal reforms of the 1970s to the current era of deep trade agreements and global trade fragmentation. It also delves into four key agreements: the Free Trade Agreement with the United States, the Free Trade Agreement with China, the Association Agreement with the European Union, and the Comprehensive and Progressive Agreement for Trans-Pacific Partnership. Finally, this study assesses the achievements, limitations, and structural challenges of Chile's trade integration, offering valuable lessons for developing economies seeking sustainable and diversified integration into the global economy.